2007
DOI: 10.1111/j.1600-0420.2006.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Principles of disability glare measurement: an ophthalmological perspective

Abstract: ABSTRACT. Disability glare describes the loss of retinal image contrast as a result of intraocular light scatter, or straylight. It has increasingly important modern implications such as with cataract and refractive surgery or high-intensity lighting. However, its measurement has proven difficult despite many varying approaches. This article aims to explain the principles and problems associated with glare testing that are important for assessment and use of glare measures. After defining disability glare, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 55 publications
3
87
0
2
Order By: Relevance
“…It is well known that developing cataracts cause increased intraocular forward light scatter, which causes visual difficulty due to loss of retinal image contrast, and this type of visual difficulty is called GD. 19,31 It has also been previously reported that the amount of scatter can be evaluated indirectly by measuring GD, 32 that GD offers a discriminative and valid measure of visual assessment in cataract, 33 including cataract with good high contrast VA in the presence of functional complaints, 34,35 that GD improves after cataract surgery, 36 and that this improvement is independent of improvement in high contrast acuity. 37 We suggest that testing mesopic and photopic GD at a medium spatial frequencies will help assess symptomatic non-advanced cataracts.…”
Section: Visual Difficulty In Symptomatic Non-advanced Cataract S Chamentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that developing cataracts cause increased intraocular forward light scatter, which causes visual difficulty due to loss of retinal image contrast, and this type of visual difficulty is called GD. 19,31 It has also been previously reported that the amount of scatter can be evaluated indirectly by measuring GD, 32 that GD offers a discriminative and valid measure of visual assessment in cataract, 33 including cataract with good high contrast VA in the presence of functional complaints, 34,35 that GD improves after cataract surgery, 36 and that this improvement is independent of improvement in high contrast acuity. 37 We suggest that testing mesopic and photopic GD at a medium spatial frequencies will help assess symptomatic non-advanced cataracts.…”
Section: Visual Difficulty In Symptomatic Non-advanced Cataract S Chamentioning
confidence: 99%
“…14,15 The questionable ecological validity of VA charts hinders interpretation of patients' functional visual difficulty following the development of an ocular disease, such as age-related macular degeneration, 16 cataract, glaucoma, and diabetic retinopathy. 17 Consequently, it has been suggested that VA is not the most appropriate tool to investigate the impact of symptomatic non-advanced cataract on visual function and experience, 11 and complementary and/or alternative techniques that have been investigated include CS, 18 glare disability (GD), 19 reading performance, 20 and functional visual difficulty assessed by various questionnaires. [21][22][23] Morphological and optical characteristics of lens opacification are also important, and can be assessed by various grading systems 24 and Scheimpflug photography, 25,26 respectively, and have the advantage of being independent of patient cooperation and ocular co-morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In most tests, especially those that involve measuring contrast sensitivity or visual acuity in the presence of a continuous, static glare source, its light may cause the pupil to constrict enough to affect the results of the glare measurement (26) .…”
Section: Disability Glarementioning
confidence: 99%
“…Addressing these issues requires methods to measure the effect of glare on a person, with and without such ophthalmic devices. Approaches include the measurement of intraocular light scatter that is responsible for disability glare and asking drivers to subjectively rate their glare problems, or the annoyance of a particular glare source (Aslam et al, 2007). Acuity or contrast sensitivity tests can also be performed with glare sources of different magnitude and different angles from the test target present (Aslam et al, 2007).…”
Section: Quantifying the Behavioral Impactmentioning
confidence: 99%